Exploring difference in land surface temperature between the city centres and urban expansion areas of China's major cities. Issue 23 (1st December 2020) - Zhao, Jiyao; Yu, Le; Xu, Yidi; Li, Xuecao; Zhou, Yuyu; Peng, Dailiang; Liu, Han; Huang, Xiaomeng; Zhou, Zheng; Wang, Dong; Ren, Chao; Gong, Peng
ABSTRACT: China has experienced rapid urbanization over the past decades, which has changed the physical environment of its urban areas. Based on Aqua/Moderate Resolution Imaging Spectroradiometer (MODIS) land surface temperature observations from the Google Earth Engine, this study focuses on the difference in daytime and night-time temperature between the city centres and the annual expansion areas of China's 34 municipalities, defined as the surface urban heat difference (SUHD), from 2002 to 2013 considering both summer and winter. Our result showed that the land surface temperature in the urban expansion areas in nearly all cities was lower than those in the city centres in three out of the four periods except for winter days. For temporal characteristics, the largest SUHD occurred in the winter night-time, followed by the summer night-time, summer daytime and winter daytime. Then we revealed spatial characteristics of SUHD on city and urban expansion region level. Cities were grouped into two major clusters based on the average temperature difference between the city centres and the urban expansion areas, exhibiting significant spatial heterogeneity. SUHD of moister cities mostly ranged from 0°C to 2°C in four different times while that of dryer cities distributed from −2°C to 4°C. Generally, the SUHD of cities with moist climates was stronger in the day but weaker at night and decreased more rapidly after land cover was urbanized. When comparing the SUHD in different expansion years, our results showed that areas that had developed earlier had a weaker SUHD. Normalized Difference Vegetation Index (NDVI) difference between urban centre and urban expansion regions and moisture were significant indicators effecting the SUHD.